1997
DOI: 10.1016/s1074-7613(00)80334-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-6 and Its Soluble Receptor in Induction of Chemokines and Leukocyte Recruitment

Abstract: IL-6-/- mice showed impaired leukocyte accumulation in subcutaneous air pouches. Defective leukocyte accumulation was not due to a reduced migratory capacity of IL-6-/- leukocytes and was associated with a reduced in situ production of chemokines. These observations led to a reexamination of the interaction of IL-6 with endothelial cells (EC). EC express only the gp130 signal transducing chain and not the subunit-specific IL-6R and are therefore unresponsive to IL-6. However, EC are responsive to a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
719
4
23

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,009 publications
(807 citation statements)
references
References 66 publications
(33 reference statements)
50
719
4
23
Order By: Relevance
“…While an overall normal inflammatory response, paralleled with three-fold higher TNF␣ levels, 24 resulted in IL-6 −/− mice after a systemic stimulus (LPS), an impaired response in these mice was observed when a local stimulus (turpentine) was used. 24,25 This is consistent with in vitro and in vivo evidence supporting the concept that the IL-6 system plays a sensitive role in local inflammatory reactions by amplifying leukocyte recruitment 26 and with the capacity of IL-6 to protect against LPS toxicity. 9,27 In summary, the data from the present study indicate that the IL-6 promoter polymorphisms studied do not play a major role as genetic susceptibility factors for RA.…”
Section: Genes and Immunitysupporting
confidence: 86%
“…While an overall normal inflammatory response, paralleled with three-fold higher TNF␣ levels, 24 resulted in IL-6 −/− mice after a systemic stimulus (LPS), an impaired response in these mice was observed when a local stimulus (turpentine) was used. 24,25 This is consistent with in vitro and in vivo evidence supporting the concept that the IL-6 system plays a sensitive role in local inflammatory reactions by amplifying leukocyte recruitment 26 and with the capacity of IL-6 to protect against LPS toxicity. 9,27 In summary, the data from the present study indicate that the IL-6 promoter polymorphisms studied do not play a major role as genetic susceptibility factors for RA.…”
Section: Genes and Immunitysupporting
confidence: 86%
“…Levels of IL-6 had a strong correlation with neurologic function and infarct size in animal experimental ischemia as well as in stroke patients (33,34). It was also demonstrated that the IL-6 system plays an important role in local inflammatory reactions by amplifying leukocyte recruitment and changing endothelial permeability (35). The ability of GPx1 to modulate the level of IL-6 is most likely due to the inhibitory effect on ROS production, which is known by several investigators to stimulate transcriptional activation of IL-6 (36,37).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, IL-6 induces endothelial expression of adhesion molecules and endothelial production of monocyte chemoattractant protein 1 (58), a chemokine responsible for monocyte recruitment. Moreover, IL-6 Ϫ/Ϫ mice show impaired leukocyte accumulation at the site of inflammation (58) and defective transition to a chronic mononuclear cell infiltrate (59). IL-6 is also involved in the recruitment of mesenchymal vascular cells and neoangiogenesis in vivo (60), and has been shown to induce proliferation of synovial fibroblasts (61).…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 99%